Remote ischaemic preconditioning protects against cardiopulmonary bypass-induced tissue injury: a preclinical study. Issue 10 (3rd July 2006) - Kharbanda, R K; Li, J; Konstantinov, I E; Cheung, M M H; White, P A; Frndova, H; Stokoe, J; Cox, P; Vogel, M; Van Arsdell, G; MacAllister, R; Redington, A N
Abstract : Objectives: To test the hypothesis that remote ischaemic preconditioning (rIPC) reduces injury after cardiopulmonary bypass (CPB). Design: Randomised study with an experimental model of CPB (3 h CPB with 2 h of cardioplegic arrest). Twelve 15 kg pigs were randomly assigned to control or rIPC before CPB and followed up for 6 h. Intervention: rIPC was induced by four 5 min cycles of lower limb ischaemia before CPB. Main outcome measures: Troponin I, glial protein S-100B, lactate concentrations, load-independent indices (conductance catheter) of systolic and diastolic function, and pulmonary resistance and compliance were measured before and for 6 h after CPB. Results: Troponin I increased after CPB in both groups but during reperfusion the rIPC group had lower concentrations than controls (mean area under the curve −57.3 (SEM 7.3) v 89.0 (11.6) ng·h/ml, p = 0.02). Lactate increased after CPB in both groups but during reperfusion the control group had significantly more prolonged hyperlactataemia (p = 0.04). S-100B did not differ between groups. Indices of ventricular function did not differ. There was a tendency to improved lung compliance (p = 0.07), and pulmonary resistance changed less in the rIPC than in the control group during reperfusion (p = 0.02). Subsequently, peak inspiratory pressure was lower (p = 0.001). Conclusion: rIPC significantly attenuated clinically relevant markers of myocardial and pulmonary injury after CPB. Transient limb ischaemia as an rIPC stimulus has potentially important clinical applications.